Copper-catalyzed radical cascade oxyalkylation of olefinic amides with simple alkanes: highly efficient access to benzoxazines. Issue 56 (29th June 2017) - Wang, Jie; Sang, Ruoyu; Chong, Xiaolong; Zhao, Yinuo; Fan, Wenjie; Li, Zejiang; Zhao, Jincan
Abstract : A copper-catalyzed C(sp 3 )–H bond functionalization of simple alkanes with olefinic amides was developed for the synthesis of benzoxazine derivatives. Abstract : A copper-catalyzed C(sp 3 )–H bond functionalization of simple alkanes with olefinic amides was developed for the efficient synthesis of important benzoxazine derivatives. It involves new C–C and C–O bond formation in one step via a radical cascade process.